Assessing the Potential Use of Porous Asphalt Pavements under Timor-Leste's Climatic Conditions (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Timor-Leste’s tropical climate, characterized by high temperatures, strong solar radiation, and seasonal heavy rainfall, poses significant challenges to conventional asphalt pavements, including rutting, moisture damage, and accelerated aging. Porous asphalt pavements, widely adopted in tropical and subtropical regions, offer enhanced drainage capacity and potential environmental benefits. This study evaluates the applicability of porous asphalt under Timor-Leste’s climatic conditions through a narrative literature review of evidence reported in comparable tropical environments. The analysis highlights the hydraulic and thermal advantages of porous asphalt, such as improved stormwater management, reduced hydroplaning risk, and potential mitigation of urban heat accumulation. However, concerns regarding durability, clogging, maintenance requirements, and economic feasibility remain critical. Findings suggest that porous asphalt could contribute to climate-resilient infrastructure in Timor-Leste, but local validation through laboratory testing, pilot-scale field studies, and life-cycle cost assessments is essential before large-scale implementation.